129 Myocardial salvage during primary PCI can be predicted in the Cath lab. (9th June 2011) - Payne, A R; Berry, C; Doolin, O; McEntegart, M B; Woodward, R; Saul, A; Robb, S D; Petrie, M C; Ford, I; Oldroyd, K G
Abstract : Objectives: This study investigated the relationship between the index of microcirculatory resistance (IMR) and myocardial salvage as determined by T2-weighted and contrast-enhanced cardiac magnetic resonance (CMR) imaging in patients undergoing primary percutaneous coronary intervention (pPCI) for ST elevation myocardial infarction (STEMI). Background: IMR is a simple invasive measure of microvascular function available at the time of pPCI. T2-weighted non-contrast CMR can reveal myocardial oedema, and in the post-infarct population this represents the ischaemic area at risk (AAR). Contrast-enhanced CMR delineates the area of myocardial infarction. The volume of myocardium within the AAR, but not contained within the infarct area is salvaged myocardium. Methods: 108 patients with STEMI underwent invasive coronary physiology measurements during pPCI and had a subsequent CMR scan at a median of 19 h post pPCI. Short axis non-contrast T2-weighted images were acquired and delayed enhancement imaging was performed following administration of intravenous gadolinium (0.1 mmol/kg). AAR was determined and myocardial salvage was calculated as AAR—infarct area. Results: IMR was 29 (21), AAR 32% (13%) and myocardial salvage 6% (9%)—all mean (SD). Spearman rank correlation between IMR and AAR was 0.27 (p 0.02) and between IMR and salvage was −0.31 (p 0.01). IMR was also a multivariate predictor of AAR (p 0.01) and a negative multivariate predictor of myocardial salvage (p 0.02). Conclusions: IMR measured acutely correlates with AAR and correlates negatively with myocardial salvage as determined by MRI.